Anatomy of a successful stewardship intervention: Improving perioperative prescribing in penicillin-allergic patients. (16th September 2022) - Sexton, Mary Elizabeth; Kuruvilla, Merin Elizabeth; Wolf, Francis A.; Lynde, Grant C.; Wiley, Zanthia
Abstract: Objective: To evaluate whether a series of quality improvement interventions to promote safe perioperative use of cephalosporins in penicillin-allergic patients improved use of first-line antibiotics and decreased costs. Design: Before-and-after trial following several educational interventions. Setting: Academic medical center. Patients: This study included patients undergoing a surgical procedure involving receipt of a perioperative antibiotic other than a penicillin or carbapenem between January 1, 2017, and August 31, 2019. Patients with and without a penicillin allergy label in their electronic medical record were compared with respect to the percentage who received a cephalosporin and average antibiotic cost per patient. Methods: A multidisciplinary team from infectious diseases, allergy, anesthesiology, surgery, and pharmacy surveyed anesthesiology providers about their use of perioperative cephalosporins in penicillin-allergic patients. Using findings from that survey, the team designed a decision-support algorithm for safe utilization and provided 2 educational forums to introduce this algorithm, emphasizing the safety of cefazolin or cefuroxime in penicillin-allergic patients without history of a severe delayed hypersensitivity reaction. Results: The percentage of penicillin-allergic patients receiving a perioperative cephalosporin improved from ∼34% to >80% following algorithm implementation and the associated educational interventions. This increase in cephalosporin use was associated with a ∼50% reduction in antibiotic cost per penicillin-allergic patient. No significant adverse reactions were reported. Conclusions: An educational antibiotic stewardship intervention produced a significant change in clinician behavior. A simple intervention can have a significant impact, although further study is needed regarding whether this response is sustained and whether an educational intervention is similarly effective in other healthcare systems.